Hydrogen bonding in molecular crystals - Thakuria, R.; Sarma, B.; Nangia, A. (Comprehensive Supramolecular Chemistry II, 2017)
The hydrogen bond is an important intermolecular interaction in chemical, biological, and materials systems. A proper understanding of noncovalent interactions, notably hydrogen bonds between molecules in supramolecular aggregates, is essential for the design of crystalline materials and new supramolecular systems with desired physical and chemical properties. The International Union of Pure and Applied Chemistry provided a broadly acceptable and yet fairly precise definition of the hydrogen bond in 2011. Knowledge of weak intermolecular interactions and hydrogen bonding has immediate applications in the discovery of new medicines and in the development of novel and biocompatible pharmaceutical products and implants for the next wave of innovations. In this article, we summarize a tutorial background of the hydrogen-bond interaction and then present examples of molecular crystals sustained by this interaction and the role of hydrogen bonding in directing the structural organization. The examples are meant to illustrate the different facets of hydrogen bonding in crystal structures, their design, and properties. We close with some of the new techniques for structure determination for very small or weakly diffracting crystals, as is often the case for supramolecular materials and pharmaceutical products.